JUVENILE HELIUM IN ARCHEAN ENDERBITES AND ALKALINE GRANITES OF THE KOLA PENINSULA - Vetrin V.R.; Kamenskii I.L.; Ikorskii S.V.; Gannibal M.A. (My University, 2003)
The He isotopic composition was studied in Archean enderbites, aluminous gneisses, and alkaline granites of the Kola Peninsula. It was shown that enderbites formed after intrusive protoliths during their granalite metamorphism presumably retained He that was trapped by crystallizing magmatic minerals. The mantle component was found in helium extracted by high-temperature (≥1450°C) annealing of fluid inclusions in accessory ilmenite from alkaline granites of the Ponoi Massif. The fluid trapped during the crystallization of alkaline granites contained 3-7% of mantle component and might have been formed by mixing of predominant crustal radiogenic He and juvenile 3He that was supplied from a deep-seated mantle source in a ratio of about (14-42) : 1.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей